2022
DOI: 10.1007/s11661-022-06846-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hot Band Annealing on Cold-Rolled Microstructure and Recrystallization in AA 6016

Abstract: The influence of an intermediate heat treatment at the end of hot rolling and before cold rolling on Cube texture formation during the final solution annealing of AA 6016 is investigated. Three hot bands with different initial grain sizes and textures are considered: the first one without annealing before cold rolling, while the other two hot bands are heat treated at 540 °C for 1 hour in air before being cold rolled. One of the heat-treated hot bands was left to cool down in air and the other inside the furna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…There is much literature discussing the evolution of the microstructure and mechanical properties of aluminum alloys after the cold rolling of specimens subjected to heat [27,28]. Some studies have reported the difference between aluminum alloys after heat treatment and those subjected to cold rolling [29,30]. However, there is a lack of discussion on different treatment implementation sequences for cold rolling and heat treatment on one Al alloy material.…”
Section: Introductionmentioning
confidence: 99%
“…There is much literature discussing the evolution of the microstructure and mechanical properties of aluminum alloys after the cold rolling of specimens subjected to heat [27,28]. Some studies have reported the difference between aluminum alloys after heat treatment and those subjected to cold rolling [29,30]. However, there is a lack of discussion on different treatment implementation sequences for cold rolling and heat treatment on one Al alloy material.…”
Section: Introductionmentioning
confidence: 99%
“…Chen [ 12 ] studied the evolution of the microstructure and properties of magnesium-alloy plates during ZK61 magnesium-alloy rolling. Texture evolution depends on rolling parameters (reduction, temperature) and deformation [ 13 , 14 ]. Accordingly, the influence of texture of ZK61 magnesium alloy in rolling state on the microstructure and properties of plate rolling is particularly important.…”
Section: Introductionmentioning
confidence: 99%